C-Gait for Detecting Freezing of Gait in the Early to Middle Stages of Parkinson’s Disease: A Model Prediction Study - Chen, Zi-Yan; Yan, Hong-Jiao; Qi, Lin; Zhen, Qiao-Xia; Liu, Cui; Wang, Ping; Liu, Yong-Hong; Wang, Rui-Dan; Liu, Yan-Jun; Fang, Jin-Ping; Su, Yuan; Yan, Xiao-Yan; et al. (Frontiers in Human Neuroscience, 2021)
Abstract Objective: Efficient methods for assessing walking adaptability in individuals with Parkinson's disease (PD) are urgently needed. Therefore, this study aimed to assess C-Gait for detecting freezing of gait (FOG) in patients with early-to middle-stage PD. Method: Patients with PD (Hoehn and Yahr stages 1-3) were recruited from April 2019 to November 2019 in Beijing Rehabilitation Hospital. The participants performed 6 items of walking adaptability on an instrumented treadmill augmented with visual targets and obstacles (C-Mill). The patient's walking adaptability was evaluated by C-Gait assessment and traditional walking tests, and FOG-related indexes were collected as outcome measures. Result: Totally 53 patients were included in this study. Most C-Gait assessment items had no or low correlations with traditional walking tests. The obstacle avoidance (r=-0.639, P=0.003) and speed of adaptation (r=-0.486, P=0.035) items could provoke FOG with high sensitivity. In addition, C-Gait assessment (AUC=0.755) had slightly better discrimination of freezers from non-freezers compared with traditional walking tests (AUC=0.672); specifically, obstacle avoidance and speed of adaptation have uniquely discriminant potential. Conclusion: C-gait assessment could comprehensively evaluate walking ability in PD patients, unlike traditional walking tests. The obstacle avoidance and speed of adaptation items in C-Gait are highly sensitive for predicting freezers among PD patients.